The Gut-Microglia Connection: Implications for Central Nervous System Diseases - Wang, Yiliang; Wang, Zhaoyang; Wang, Yun; Li, Feng; Jia, Jiaoyan; Song, Xiaowei; Qin, Shurong; Wang, Rongze; Jin, Fujun; Kitazato, Kaio; Wang, Yifei (Frontiers in Immunology, 2018)
The importance of the gut microbiome in central nervous system (CNS) diseases has long been recognized; however, research into this connection is limited in part by a lack of convincing mechanisms as the brain is a distant target of the gut. Historically studied by researching the brain revealed that of the CNS diseases affected by the gut microbiome, most are also closely associated with the dysfunction of microglia. Microglia, the major CNS-resident macrophages, are crucial for the immune response of the CNS against infection and injury, as well as for brain development and function. However, the current understanding of the mechanisms controlling the maturation and function of microglia is obscure, especially extrinsic factors affecting the function of the microglia during the developmental process. It has been recently revealed that gut microflora significantly influences microglia from before birth until adulthood and the metabolites generated from gut microbiota regulate the inflammation response mediated by microglia in CNS; this inspired our hypothesis that microglia may act as a critical mediator to link the gut microbiome and CNS diseases. Herein, we highlight and discuss recent findings that show the influence of host microbiome, as a crucial extrinsic factor, on the microglia within the CNS. In addition, we summarize the CNS diseases associated with both the host microbiome and microglia and explore the potential pathway that gut bacteria participated in. Our work thus provides a comprehensive theoretical foundation for the study of the gut-microglia connection in the development of CNS diseases; this provides great potential for researchers to overcome CNS diseases by targeting pathways associated with the gut-microglia connection.